ACESSO E PERMANÊNCIA DO ESTUDANTE COM TRANSTORNO DO ESPECTRO AUTISTA (TEA) NAS UNIVERSIDADES FEDERAIS DO CENTRO-OESTE DO BRASIL - Andre Luiz Alvarenga de Souza (2023)
This study aims to analyze how access and retention of students diagnosed with Autism Spectrum Disorder (ASD) is covered in the Institutional Development Plans (PDIs) of Federal Universities located in the Central-West region of Brazil. For this, the following institutions were selected: University of Brasília (UnB), Federal University of Goiás (UFG), Federal University of Mato Grosso (UFMT) and Federal University of Mato Grosso do Sul (UFMS). Brazilian legal provisions related to special and inclusive education in Higher Education were also considered. The specific objectives of this investigation include: 1) characterizing the development of individuals with ASD based on scientific reviews on the topic; 2) analyze access and retention policies in Higher Education, identifying data relating to students with ASD at Federal Public Universities in the Central-West region of Brazil and 3) examine documents from Higher Education institutions on the inclusion policy for students with ASD TEA, as well as the actions implemented to guarantee access and retention of these students. Access to education for people with ASD represents an advance in Brazil's educational history, however there are barriers to learning and participation for these students, which impact their academic routine at Public Universities. The methodology used involved the use of bibliographic review and document analysis techniques, focusing on the analysis of policies and programs that guide and standardize Higher Education, considering historical-dialectical materialism. The results obtained allowed us to identify that access for students with disabilities is achieved through the Quota Law and their retention is encouraged by existing programs in the researched institutions, contributing to the completion of the course. It was also noticed that both Brazilian legal provisions and the PDIs of the selected Universities present specific actions to assist students with ASD. However, there are gaps that require review and improvement, aiming to provide conditions so that autistic students can complete their course successfully.